Legal Analysis Of Crime Advocates Who Commit Crimes In Carrying Out Their Duties And Professions - Yasir Habiebie (International Asia Of Law and Money Laundering (IAML), 2022)
In achieving a good legal order law enforcement in Indonesia is run by law enforcement officers consisting of judges, prosecutors, police, and also advocates. Advocate is one of the law enforcement officers, currently advocates in carrying out their profession regulated in Law Number 18 of 2003 on advocates. In fact, there are also advocates who are indicated to have committed crimes in carrying out their duties and professions as happened in 2010 where two lawyers were named as suspects. Crimes that can be committed by an advocate in carrying out his duties and profession actually all crimes can be committed by anyone if the control within the person is very weak and specifically related to the duties and profession of an advocate of course the crime is a crime related to the duties and profession of an advocate in law enforcement bribery. against several other law enforcement authorities and witnesses.